(untitled) (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY To assess the performance of the Expanded Risk Score in Rheumatoid Arthritis (ERS-RA), a disease-specific cardiovascular disease (CVD) prediction score, in evaluating the 10-year risk, in comparison with other traditional algorithms in patients with rheumatoid arthritis (RA). METHODS Consecutive RA patients, aged 40–75 years, without established CVD, were included. We calculated the disease-specific ERS-RA and four traditional CVD prediction scores: the modified Systematic Coronary Risk Evaluation (mSCORE), the Framingham Risk Score using body mass index (FRS BMI), the calculator developed by the American College of Cardiology / American Heart Association in 2013 (ACC/AHA 2013) and the QRISK3. Subjects also underwent ultrasound assessment of the carotid arteries. The presence of a carotid intima-media thickness (CIMT) >0.90 mm or of carotid plaques identified the high-risk patients. RESULTS Of the 84 patients evaluated, 33 (39.3%), 16 (19.0%), 24 (28.6%), 25 (29.8%) and 33 (39.3%) subjects were defined as having high CVD risk according to ACC/AHA 2013, mSCORE, FRS BMI, QRISK3 and ERS-RA, respectively. Compared with the ultrasound results, all the areas under the receiver operating characteristic curves (AUC-ROC) showed good discrimination properties (0.848 – FRS BMI, 0.816 – mSCORE, 0.828 – ACC/AHA 2013, 0.844 – QRISK3, 0.869 – ESR-RA). Comparison of the AUC-ROCs did not show that discriminative ability for detecting subclinical atherosclerotic damage was improved with ESR-RA. CONCLUSIONS Using a surrogate marker of subclinical atherosclerotic organ damage as indicator of CVD burden, the newly ERS-RA risk score that incorporates specific aspects of RA performs as well as ACC/AHA 2013, mSCORE, FRS BMI and QRISK3 estimators.